Frontline employees' participation in service innovation implementation: The role of perceived external reputation. Issue 5 (October 2016) - Schaarschmidt, Mario
Abstract: Drawing on expectancy theory and social exchange theory, this study investigates how employees' perceived external reputation is associated with their willingness to participate in service innovation implementation. Data from 150 German and more than 200 American frontline service employees supports the notion that the link between perceived external reputation and service innovation implementation behavior is mediated by expected reputation gains and expected positive performance outcomes. In addition, expected positive performance outcomes seem to be a stronger driver than expected reputation gains in the American sample. The authors conclude this study by highlighting its implications for both theory and management practice.